Emerging Fixation Technique to Prevent Pectus Bar Displacement: Needlescope-Assisted 3-Point Fixation - Yoo, Gyeol; Rha, Eun Young; Jeong, Jin Yong; Lee, Jongho; Sim, Sung Bo; Jo, Keon Hyon (The Thoracic and Cardiovascular Surgeon, 2016)
Background Bar flipping displacement is one of the most common complications after the Nuss procedure for pectus excavatum. We evaluated the results of a modified Nuss procedure with needlescope-assisted bar fixation.Methods The records of 41 patients with pectus excavatum who underwent single pectus bar insertion with the Nuss procedure between July 2011 and August 2014 were retrospectively reviewed. The patients were divided into two groups: those who did not undergo 3-point fixation (group A) and those who did undergo 3-point fixation (group B).Results There were 36 male patients and 5 female patients with a mean age of 10.7 ± 8.3 years (range: 3–36 years). The postoperative Haller index (HI) (2.61 ± 0.42) was significantly lower than the preoperative HI (3.91 ± 1.07; p < 0.01). The angle of the initial bar position was 5.59 ± 7.37 degrees in group A and 8.52 ± 9.61 degrees in group B, with no significant difference between the groups (p > 0.05). The rate of reoperation to correct bar displacement was lower in group B (3.3%) than in group A (9.1%).Conclusion Needlescope-assisted 3-point fixation of the bar was performed without an additional skin incision and showed a low rate of reoperation to correct displacement of the pectus bar.
Keywords: pectus excavatum; Nuss procedure; thoracoscopy/VATS; complication; bar displacement